1983
DOI: 10.1111/j.1365-2125.1983.tb04980.x
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of genetically determined oxidation status to inter‐ individual variation in phenacetin disposition.

Abstract: 1 The oxidative O-de-ethylation and aromatic 2-hydroxylation of phenacetin have been investigated in panels of extensive (EM, n = 13) and poor (PM, n = 10) metabolizers of debrisoquine. 2 The EM group excreted in the urine significantly more paracetamol (EM: 40.8 + 14.9% dose/0-8 h; PM: 29.2 + 8.7% dose/0-8 h, 2P < 0.05) and significantly less 2-hydroxylated metabolites (EM: 4.7 + 2.3% dose/0-8 h; PM: 9.7 + 3.5% dose/0-8 h, 2P < 0.005) than the PM group.3 Apparent first-order rate constants, calculated from po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Early evidence for genetic variability on CYP1A2 was first noted when a familial defect in O -deethylation, a marker reaction for CYP1A2 , was reported more than four decades ago (Devonshire et al 1983; Shahidi 1967). More recently, it has been shown that monozygotic twins share closer kinetic profile than dizygotic twins for caffeine metabolism, with an estimated heritability of 0.725 (Rasmussen et al 2002).…”
Section: Genetics and Caffeine Responsementioning
confidence: 99%
“…Early evidence for genetic variability on CYP1A2 was first noted when a familial defect in O -deethylation, a marker reaction for CYP1A2 , was reported more than four decades ago (Devonshire et al 1983; Shahidi 1967). More recently, it has been shown that monozygotic twins share closer kinetic profile than dizygotic twins for caffeine metabolism, with an estimated heritability of 0.725 (Rasmussen et al 2002).…”
Section: Genetics and Caffeine Responsementioning
confidence: 99%
“…In this regard, cigarette smoking has been shown to induce hepatic P-450PA levels in human liver and to increase microsomal phenacetin O-deethylase activity (21), which is catalyzed selectively by human P-450PA (16). In addition, a genetic polymorphism for phenacetin O-deethylation has been described, with 5-10% of the population deficient in this activity (22).[The evidence that human P-450PA, the phenacetin 0-deethylase, is the product of the human P450IA2 gene is as follows: antibodies raised to rat P-450ISF-G (P-450IA2) or human P-450PA recognize a single polypeptide in human liver microsomes and inhibit microsomal phenacetin 0-deethylase activity; the level of immunoreactive protein is highly corAbbreviations: P-450, cytochrome P-450; ABP, 4-aminobiphenyl; N-OH, N-hydroxy; 13X, 1,3-dimethylxanthine (theophylline); 17X, 1,7-dimethylxanthine (paraxanthine); 37X, 3,7-dimethylxanthine (theobromine); 137U, 1,3,7-trimethyluric acid; 2-NA, 2-naphthylamine; Glu-P-1, 2-amino-6-methyldipyrido[1,2-a:3',2'-d]imidazole; IQ, 2-amino-3-methylimidazo[4,5-f]quinoline; Trp-P-2, 3-amino-1-methyl-5H-pyrido [4,3-b]indole. §To whom reprint requests should be addressed.…”
mentioning
confidence: 99%
“…In this regard, cigarette smoking has been shown to induce hepatic P-450PA levels in human liver and to increase microsomal phenacetin O-deethylase activity (21), which is catalyzed selectively by human P-450PA (16). In addition, a genetic polymorphism for phenacetin O-deethylation has been described, with 5-10% of the population deficient in this activity (22).…”
mentioning
confidence: 99%
“…Clinical pharmacokinetic investigations and studies with human liver microsomes have indicated that the O-deethylation of phenacetin is impaired among poor debrisoquine hydroxylators (Davies et al, 1981;Devonshire et al, 1983). Presumably, the same isozyme of P-450 in human liver catalyzes the oxidation of both phenacetin and debrisoquine.…”
Section: Discussionmentioning
confidence: 99%